The Politics of Demographic Change: Addressing the Youth Bulge in Ivory Coast - Hamdi, Farhan (As- Sakinah Law Firm & Society of Visual Informatics, 2023)
This research explores the relationship between youth bulge and political instability, using Ivory Coast as a case study. Despite being one of the world's poorest continents, Africa is experiencing a quick and considerable youth bulge, posing difficulties to political stability. The youth bulge phenomenon, which is defined by a disproportionate increase in the youthful population compared to other age groups, has historically been linked to political upheaval, as evidenced by events such as the Arab Spring. Lack of democracy, economic restrictions, and ethnic or religious discrimination are among the factors that contribute to political instability during a youth bulge. This study uses a qualitative research approach and secondary data analysis to investigate the impact of the youth bulge on the Ivory Coast political scene. The findings suggest a high youth unemployment rate of 35.7%, as well as considerable differences in educational access and political participation among young people. This lack of political engagement exacerbates the confusion, resulting in rebellion and instability. The study emphasizes the significance of tackling socioeconomic difficulties and increasing political inclusion to counteract the negative consequences of the youth bulge on political stability in Ivory Coast and other contexts.